(untitled) (Journal of Tikapur Multiple Campus, 2015)
The major objectives of the present study is to identify human rights friendly, unfriendly and paradoxical subject matters included in primary education curriculum and analyze opinions of primary school teachers, students, parents, curriculum designers, and stakeholders of primary education on existing primary education curriculum. Accordingly, desk review and survey method is used in the present study to carry out this research. Respondents of the present study expressed mixed views (positive and negative) on the inclusion of human right education into school curricula and text books and their implementation. However, very few numbers of participants of the workshops spoke against human right education. They were of the view that of human right education contents could be more meaningful and effective if such contents were included in school curricula and textbooks by dealing rights and duties with equal importance. Thus, human right education based primary education curriculum is the urgent need of Nepal but the curriculum should be balanced form all angle.